Ações formativas voltadas aos(às) diretores(as) de escolas públicas de educação básica no governo Haddad (2013-2016) - Silva, Vagnum Dias da (2019)
This research was aimed at analyzing formative actions directed to school principals who worked within the São Paulo Municipal Education Bureau, between the years of 2013-2016, during the Workers' Party mayor Fernando Haddad administration. Our interest was to identify the premises on which such actions were structured. Regarding a Workers' Party administration, the hypothesis was that such actions would be based on democratic principles, mainly autonomy and participation, and not on technicalist and managerial approaches, very much in vogue nowadays. A research relevant aspect was the attempt to discern between two main aspects of the actions: school routines and others, linked to permanent, lifelong formation processes, which structure schools' administration, considering both essentials to the offering of social qualified basic education. The methodology was qualitative and exploratory, based on documental sources related to the formative actions carried on in the Regional Office of Education of São Miguel Paulista, linked to the São Paulo Municipal Education Bureau and the governmental plan for basic education in the city of São Paulo, Programa Mais Educação São Paulo: subsídios para implantação (SÃO PAULO, 2014). Thus, through this investigation, it was possible to comprehend that there was some congruency between the basic educational proposals from the Workers' Party and the formative actions in which the principals took part, and, still, that democratic principles, such as autonomy and participation were part on them.